Efficacy of Biophotonics Therapy in Viral and Microbial Illnesses in the 21st Century - Einstein, George P.; Tulp, Orien L. (British Journal of Healthcare and Medical Research, 2023)
The application of biophotonic therapies has been in clinical use on a limited basis for many decades, having recognized that ultraviolent radiation can be lethal to viruses and microorganisms, but had been nearly forgotten since the discovery and further development of antimicrobial and antiviral medications now in common use virtually replaced biophotonic therapy. While the advancement of chemical based antimicrobial and antiviral agents enabled highly effective therapies against infectious illnesses, and undoubtedly saved many lives who might otherwise have succumbed to the infectious agents over several generations, it soon became apparent that the infectious agents often developed internal mechanisms to repel or inactivate the chemical agents, a phenomena now considered as antimicrobial resistance, and when present enabled the infectious agent to flourish even in the presence of the once effective agent, often with the most dire of clinical outcomes. In addition, patients may also develop intolerance to the prescribed agent due to allergic or other untoward responses to the therapeutic agent thereby compounding the desired treatment regimen. Biophotonic therapy utilizes photons similar to naturally obtained sunlight origins to deactivate the genomic replication processes of infectious agents, while enhancing parameters of the host’s immunologic responses. Thus, biophotonic therapy can result in an immunologic-centered vs a chemically-centered mechanism to overcome the infectious agent without side effects, typically without the development of viral or microbially-mediated resistance mechanisms by the infectious agent, and the revival and reemergence of biophotonic therapy offers a new and potentially life-saving and time proven safe and easily administered approach particularly when addressing drug-resistant infectious agents in the 21st century.